Pharmacists', General Practitioners' and Consumers' Views on Integrating Pharmacists into General Practice. - Freeman, Christopher; Cottrell, W. Neil; Kyle, Greg; Williams, Ian D.; Nissen, Lisa (Journal of Pharmacy Practice & Research, 2012)
Background: Integrating pharmacists into general practice is not a novel concept. However, it is new to Australia and evidence supporting this role is limited. Aim: To seek the views of pharmacists, general practitioners and consumers on integrating pharmacists into general practice. Method: Questionnaires were used to elicit the opinions of pharmacists, general practitioners and consumers on integrating pharmacists into general practice. Results: 1038 participants (829 pharmacists, 167 consumers, 42 general practitioners) completed the survey. Commonly agreed roles for pharmacists in general practice included drug information and medication review. Perceived barriers to service provision included the pharmacist's clinical ability and turf protection. Remuneration was viewed as a facilitator and a barrier. Perceived facilitators included additional training for pharmacists and an existing rapport with the general practitioners. Conclusion: There was support for integrating pharmacists' professional activities into general practice. These findings will guide the development of a new model of integrated primary care with practice pharmacists.